2001
DOI: 10.1159/000045978
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Calcium Oxalate Binding Proteins: Effect of Lipid Peroxidation

Abstract: Objective: Urolithiasis and free radicals have long been associated. In this study, we have isolated calcium oxalate monohydrate (COM) binding proteins from rat kidney before and after lipid peroxidation (LPO) and studied its properties on calcium oxalate crystal growth. Materials and Methods: LPO was carried out using t-butyl hydroperoxide, cumene hydroperoxide and an ascorbate system. The COM binding proteins from control and peroxidised tissues were isolated using a modified procedure. Protein was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In our laboratory, we documented an in vitro oxidative modification of a 45 kDa protein that we had isolated [24]. This finding suggests that loss of -SH groups has a profound effect on inhibitory properties in a crystallizing medium [25]. This indicates that vitamin E mediates its action on protein kinetic behaviour primarily by curbing oxidative damage to the protein of the human subjects in vivo.…”
Section: Beneficial Effect Of Vitamin E Supplementation 1413mentioning
confidence: 99%
“…In our laboratory, we documented an in vitro oxidative modification of a 45 kDa protein that we had isolated [24]. This finding suggests that loss of -SH groups has a profound effect on inhibitory properties in a crystallizing medium [25]. This indicates that vitamin E mediates its action on protein kinetic behaviour primarily by curbing oxidative damage to the protein of the human subjects in vivo.…”
Section: Beneficial Effect Of Vitamin E Supplementation 1413mentioning
confidence: 99%
“…Azelaic acid would have two important anti-atherogenic properties: one, as other dicarboxylic acids, it would have great affinity for calcium and precipitate calcium in lipid-rich domains [219][220][221][222]. This might account for the unusually high calcification associated with lipid core domains.…”
Section: Azelaic Acid a Lipid Peroxidation-derived Lipophilic Dicarbmentioning
confidence: 99%
“…For most human diseases, increased formation of reactive oxygen species is secondary to primary disease process (2). Similarly association of urolithiasis and free radicals has been reported (3). Experiments performed on animals (3,4), cultures (5) and human sera (6) have revealed that there is presence of enhanced oxidative stress in stone forming conditions.…”
Section: Introductionmentioning
confidence: 83%
“…Experiments performed on animals (3,4), cultures (5) and human sera (6) have revealed that there is presence of enhanced oxidative stress in stone forming conditions. Oxalate is known to induce lipid peroxidation by unknown mechanism which causes disruption of the structural integrity of the membranes (3,7). Superoxide dismutase (SOD) is an inbuilt defense mechanism to fight back peroxidative stress.…”
Section: Introductionmentioning
confidence: 99%